A Protein Critical for a Theiler’s Virus-Induced Immune System-Mediated Demyelinating Disease Has a Cell Type-Specific Antiapoptotic Effect and a Key Role in Virus Persistence - Ghadge, Ghanashyam D. (American Society for Microbiology, 1998)
TO subgroup strains of Theiler’s murine encephalomyelitis virus (TMEV) induce a persistent central nervous system infection and demyelinating disease in mice. This disease serves as an experimental model of multiple sclerosis (MS) because the two diseases have similar inflammatory white matter pathologies and because the immune system appears to mediate demyelination in both processes. We previously reported (H. H. Chen, W. P. Wong, L. Zhang, P. L. Ward, and R. P. Roos, Nat. Med. 1:927–931, 1995) that TO subgroup strains use an alternative initiation codon (in addition to the AUG used to synthesize the picornavirus polyprotein from one long open reading frame) to translate L*, a novel protein that is out of frame with the polyprotein and which plays a key role in the demyelinating disease. We now demonstrate that L* has antiapoptotic activity in macrophage cells and is critical for virus persistence. The antiapoptotic action of L* as well as the differential translation of L* and virion capsid proteins may foster virus persistence in macrophages and interfere with virus clearance. The regulation of apoptotic activity in inflammatory cells may be important in the pathogenesis of TMEV-induced demyelinating disease as well as MS.